Spanish preverbal subjects and the cartography of the Spanish left periphery - Martín, Juan (Lingua, 2022)
•All preverbal positions in Spanish belong to the Complementizer field.•The complementizer field is divided between a topic field and a focus field.•Spec-of-FocP acts as a subject of predication position for the focus field.•All arguments, but Non DMOs, can occupy the preverbal FocusP adjacent to the verb.•Any element on Spec-of-FocusP may trigger pseudo-distributivity effects in Spanish. In this article, after reviewing arguments for and against a preverbal dedicated subject position in Spanish, I conclude that the only asymmetry among preverbal arguments is between non-Differently Marked Objects (DMOs) and other arguments. Non DMOs cannot occupy the preverbal Focus Phrase adjacent to the verb, except for some quantified expressions. All the preverbal positions belong to the Complementizer field since the verb in Spanish always moves at least to FocP to check a [uFocus] feature. Evidence that the position to which the Spanish verb moves is Foc is given by the fact that its specifier may be occupied by indefinite nominal expressions, which are rhematic by definition, wh-words, and negative words, and by word order facts based on the syntactic position of adverbs and floating quantifiers. The Spec-of-FP acts as a subject of predication position for the focus field, and is an escape-hatch for postverbal elements, and it is argued that apart from move operations outside the clause it may serve as a step for phrases moving to the Contrastive Topic position. Elements occupying the Spec-of-FP check criterial features, and quantificational features. Finally, it is argued that in Spanish the element occupying Spec-of-FP may trigger pseudo-distributivity effects.